1998
DOI: 10.1097/00006842-199805000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Social Separation, Housing Relocation, and Survival in Simian AIDS

Abstract: The results indicate that psychosocial experiences that likely produce a stressful state are associated with shorter survival in SIV-infected monkeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 51 publications
(62 reference statements)
0
33
0
1
Order By: Relevance
“…Alternatively, changes observed in this intervention may have been due to the supportive environment created by the group setting [70]. Prior work revealed that social separation, known to be related to glucocorticoid elevations, is associated with shorter survival time among rhesus monkeys inoculated with Simian Immunodeficiency Virus [71]. Cortisol changes during CBSM may have been due to the fact that the group worked to offset the sense of isolation and personal losses (e.g., due to multiple bereavements) that many of the men were dealing with.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, changes observed in this intervention may have been due to the supportive environment created by the group setting [70]. Prior work revealed that social separation, known to be related to glucocorticoid elevations, is associated with shorter survival time among rhesus monkeys inoculated with Simian Immunodeficiency Virus [71]. Cortisol changes during CBSM may have been due to the fact that the group worked to offset the sense of isolation and personal losses (e.g., due to multiple bereavements) that many of the men were dealing with.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 13 seropositive animals (4 females, 9 males) with a range of antibody titres were brought indoors and same-sex pair-housed with an animal unknown to them. Changes in housing conditions and pairing with an unknown animal are known stressors for macaques (Capitanio & Lerche, 1998). One animal, 29937, was included in two phases of the group 1 study (described below).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, when animals are exposed to chronic aversive stimuli (e.g., cues leading to the perceived exposure to predators in an environment devoid of shelter), or an inability to perform behaviors normally essential to survival or reproduction in the wild (e.g., dispersal in mice; Latham and Mason 2004), they are likely to be stressed (Olsson and Dahlborn 2002). Indeed, the inability to predict or control stimuli that are themselves non-life-threatening can lead to chronic states of stress that can markedly decrease immunocompetence (e.g., social disruption in rhesus; Capitanio and Lerche 1998) or even lead to spontaneous mortality (e.g., foot shock in rats; Weiss 1970). One of the fundamental aims of enrichment, therefore, is to allow the animal to perform species-typical behaviors that return control over the environment to the animal and promote homeostasis.…”
Section: Potential For Abnormal Behavior To Affect Experimental Outcomesmentioning
confidence: 99%